Mechanisms of Hearing Loss in a Guinea Pig Model of Superior Semicircular Canal Dehiscence - Bu-Sheng Tong; Zi-Yu He; Chen-Ru Ding; Juan-Mei Yang; Jing Wang; Zhao Han; Yi-Bo Huang; Na Gao; Xian-Hao Jia; Fang-Lu Chi; Dong-Dong Ren (Neural Plasticity)
Defective acoustic transmission in the cochlea is closely related with various auditory and vestibular symptoms. Among them, semicircular canal dehiscence (SCD) with a defective semicircular bone is typical. Currently, the pathogenesis of SCD is usually explained by the third window hypothesis; however, this hypothesis fails to explain the variability in the symptoms and signs experienced by superior SCD (SSCD) patients. We evaluated the mechanism of hearing loss in a guinea pig model of bony dehiscence with various sizes and locations along the superior semicircular canal. Auditory brainstem responses (ABRs) and laser Doppler velocimetry were used to measure hearing loss and vibration changes before and after fenestration, as well as after restorative patching. ABR thresholds at low frequencies (e.g., 1000 Hz) increased after fenestration and decreased back to the normal range after we repaired the defect. Energy leakage from the surgically introduced third window was detected in the range of 300–1500 Hz, accompanied by increased vibration at the umbo, stapes head, and the dehiscence site, while decreased vibration was observed at the round window membrane in the same frequency range. After the patching procedure, the deviant vibrations were recovered. The degree of postfenestration energy leakage was proportional to the size of fenestration and the proximity of the fenestration site to the oval window. These results suggest that the bony fenestration of the superior semicircular canal mimics the hearing loss pattern of patients with SSCD. The decrease in perilymph wave impedance likely accounts for the auditory changes.